Malignant melanoma of the mucosa - Sarra, Luis D; Rancati, Alberto O; Butto, D; Ahumada, Juan C; Suárez Anzorena, Francisco J (Cirugía del Uruguay, 1995)
proxima/e/y 5% of malignan/ melanomas belong to non cutaneous locations; 75-80% are ocular melanomas and the rest 20-25% /acate in mucosas. Thera are described in vulva, their most frequent location, vagina, anal duct, nasal phosae, oral cavity, paranosa/ sinus, penis, esophagus and bronchi. We make in this comunica/ion clinical and histopathological considerations about malignan/ melanoma in mucosae, and present short comments of each one of the different locations. Seven cases arre presented, one of nasal phosae melanoma, one of anal duct and five of oral cavity.